2015
DOI: 10.1016/j.prevetmed.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Cow-specific risk factors for clinical mastitis in Brazilian dairy cattle

Abstract: Information related to mastitis risk factors is useful for the design and implementation of clinical mastitis (CM) control programs. The first objective of our study was to model the risk of CM under Brazilian conditions, using cow-specific risk factors. Our second objective was to explore which risk factors were associated with the occurrence of the most common pathogens involved in Brazilian CM infections. The analyses were based on 65 months of data from 9,789 dairy cows and 12,464 CM cases. Cow-specific ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
40
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 44 publications
12
40
1
3
Order By: Relevance
“…Only one study was found in the recent indexed literature describing the CM profile in Brazilian dairy herds (OLIVEIRA et al, 2015). However, the estimation of CM was expressed as incidence risk (or cumulative incidence) as opposed to rate as we did, and the evaluation was performed at the cow-level, not at the quarter-level as in the current study.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Only one study was found in the recent indexed literature describing the CM profile in Brazilian dairy herds (OLIVEIRA et al, 2015). However, the estimation of CM was expressed as incidence risk (or cumulative incidence) as opposed to rate as we did, and the evaluation was performed at the cow-level, not at the quarter-level as in the current study.…”
Section: Discussionmentioning
confidence: 95%
“…Only one recent study characterizing CM in dairy herds in Brazil were found in the indexed literature, in which the mean annual incidence risk in primiparous cows was 27%, while for multiparous cows it was 31% (OLIVEIRA et al, 2015). Indices associated with the frequency of CM, such as prevalence, incidence rate, recurrence of cases, most prevalent etiological agents, and the association of such indices with herd-level descriptors were not found for dairy herds in Brazil.…”
Section: List Of Figuresmentioning
confidence: 98%
See 3 more Smart Citations